Sustainability of biodiesel production using immobilized enzymes: A strategy to meet future bio‐economy challenges. (9th June 2022) - Raza, Mohsin; Ali, Labeeb; Inayat, Abrar; Rocha‐Meneses, Lisandra; Ahmed, Shams Forruque; Mofijur, Md; Jamil, Farrukh; Azimoh, Chukwuma Leonard
Summary: Biodiesel is an evolving energy substitute for petroleum‐based fuel products. In terms of antropogenic impacts, it is an environmentally friendly and sustainable energy source. Biodiesel is produced from a wide variety of biomass materials and its production costs are mainly related to the feedstock and production process. Transesterification is the most commonly used method for biodiesel production. Enzymatic transesterification using lipase‐enzyme has certain advantages over acid‐alkaline transesterification. The issues relating to enzyme stability, separation, and recyclability in enzymatic transesterification are further improved using immobilized enzymes. Here, we review the potential of immobilized‐enzyme technology in biodiesel production as a safer strategy to meet the needs of a sustainable future economy and will conduct future research studies. We critically analyze the state‐of‐the‐art and latest research on the production of biodiesel using immobilized lipase enzymes. Results indicate that liquid lipase's immobilization increases the stability, reactivity, and reusability and significantly decreases biodiesel production costs